2015
DOI: 10.1007/s00259-015-3075-9
|View full text |Cite
|
Sign up to set email alerts
|

Gene transcript analysis blood values correlate with 68Ga-DOTA-somatostatin analog (SSA) PET/CT imaging in neuroendocrine tumors and can define disease status

Abstract: (68)Ga-SSA PET imaging parameters (SUVmax) correlated with a circulating NET transcript signature. Disease status could be predicted by an elevated quotient of gene expression (MORF4L2) and SUVmax. These observations provide the basis for further exploration of strategies that combine imaging parameters and disease-specific molecular data for the improvement of NET management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 44 publications
(64 reference statements)
1
19
0
Order By: Relevance
“…¶ Urinary bladder mean residence time is for 2-h voiding model. between imaging and biomarkers has also been highlighted in other studies (28,29) and suggests that additional multianalyte biomarkers such as circulating NET gene transcripts should be considered in the future (30).…”
Section: Discussionmentioning
confidence: 98%
“…¶ Urinary bladder mean residence time is for 2-h voiding model. between imaging and biomarkers has also been highlighted in other studies (28,29) and suggests that additional multianalyte biomarkers such as circulating NET gene transcripts should be considered in the future (30).…”
Section: Discussionmentioning
confidence: 98%
“…However, a possible limitation of these studies is that the data on molecular features used for the correlation refer to the tumour tissue, which represents a static picture of the disease at the time of surgery and may be insufficient to predict disease evolution. In this regard the work by Bodei and colleagues is novel because the NET fingerprint analysed and correlated with the imaging parameters is a panel of blood circulating transcripts [1]. The monitoring of tumour-specific markers in the blood holds promise for a more dynamic and reliable approach to following disease progression, and increases the possibility of adding prognostic value to the molecular imaging analysis.…”
mentioning
confidence: 99%
“…In their work, Bodei and colleagues evaluated the concordance between the 68 Ga-SSA-PET and the expression of a panel of 51 blood circulating RNA transcripts (NETest) previously established as having high sensitivity and specificity in identifying NETs. They found that imaging parameters (including SUVmax) correlate well with the levels in the blood of some of the NET fingerprint genes and that the combination of imaging with the measurement of some of these blood biomarkers may help to better differentiate progressive from stable diseases [1].…”
mentioning
confidence: 99%
See 2 more Smart Citations